Bicycle-metro integration in a growing city: The determinants of cycling as a transfer mode in metro station areas in Beijing. (May 2017) - Zhao, Pengjun; Li, Shengxiao
Highlights: Travel distance is the most important influence on cycling as a transfer mode in metro station areas. A higher level of mixed land use or green parks in metro station areas is related to more cycling. Public bike-sharing program plays a significantly positive role in promoting cycling. Individual attitudes towards bicycle and car use have impacts on bicycle-metro integration. Middle- and high-income earners were more likely to drive than cycle. Abstract: Bicycle-transit integration, in which cycling is used to as a transfer mode to/from transit station is widely believed to be one very important way of promoting a transit city and achieving efficient and sustainable urban transport systems. However, the empirical evidence for the determinants of people's choices to transfer by bicycle as a travel mode remain largely unstudied. This paper investigates this issue, using Beijing and its metro system as a case study. Using a multilevel logistic model, we found that travel distance is the most important influence on rates of cycling for transfer trips between metro stations and home or workplace. There were also socioeconomic influences, with young people being less likely to cycle and more likely to use buses. Middle- and high-income earners were more likely to drive than cycle, while low-income earners were more likely to take the bus. Personal attitudes are also influential—those who prefer cheap travel were more likely to cycle. Above results suggest that the increasing city size and urban expansion are great challenges to cycling systems in growing cities. The presence of bicycle-sharing programs, mixed land use, and green parks in metro station areas were associated with greater rates of cycling transfer. In order to promote Bicycle-and-Ride schemes in metro station areas, education initiatives designed to influence behavior should be integrated with investment in bicycle infrastructure.